STRONGYLOIDES STERCORALIS ASSOCIATED WITH NEPHRITIC SYNDROME IN A CHILD WITH INTESTINAL NEURONAL DYSPLASIA - Marcos, Luis A (2007)
Strongyloidiasis, caused by Strongyloides stercoralis, is a serious Public Health problem in Peru. We report the case of a two-year-old boy who was admitted at the Instituto Especializado de Salud del Niño in Lima with a diagnosis of intestinal obstruction associated with fifteen days of diarrhea, fever and cough. The histopathological examination of the necrotic tissue of colon showed intestinal neuronal dysplasia. During his hospitalization (12 days later) he presented hypereosinophilia (with 3,460 eosinophils/mm3), cough, fever and abnormal chest x-ray. Five days later, the eosinophil count reached up to 34,286 cells/mm3. One day later, S. stercoralis larvae were found in a direct stool smear. Serology tests for HTLV-1 and HIV were negative. Interestingly, our patient presented microscopic hematuria and high blood pressure during the highest levels of eosinophils in blood, therefore acute glomerulonephritis was suspected. Treatment with thiabendazole was readily started, and administered during seven days. After that, clinical findings disappeared and larvae were no longer detected in stool examinations. The patient was asymptomatic at discharged. This case presents strong evidence to be a hyperinfection of due to autoinfection triggered by the surgery as a stress factor.